Responsible public procurement: A proposal for Innovation and Development indicators - Bragado López, Virginia; Enciso Yzaguirre, Vicente Luis; Muñoz Del Nogal, Noelia (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
Public contracting has a significant impact on the whole of the national productive activity of goods and services: both as a stimulus for its activity, and as an element of obligatory reference for the future allocation of resources, as well as in the strategic development of organizations and companies. As a continuation of a previously published study (Bragado et al., 2019) and as the objective of this new study, we are going to establish the concept of innovation and development in European contractual regulations, its transposition into national legislation and, finally, the identification of possible indicators of innovation and development.